KEBIJAKAN PEMIDANAAN KORPORASI DALAM TINDAK PIDANA PENCUCIAN UANG - Sakeus Ginting (University of Udayana, 2012)
This research aims to analyze the corporation as a legal subject and conviction of thecorporation in money laundering. The type of this research is a normative juridicalresearch. Approach to the problem approach with statue approach, analytical andconceptual approach, historical approach and comparative approach. Sources oflegal materials used is the primary legal materials and secondary legal materials.Analysis of legal materials be descriptive-analytical, evaluative, interpretive,systematic, comparative and argumetatif. In The Act No. 8 of 2010 concerningPrevention and Eradication of Money Laundry, the Corporation declared as a legalsubject that can be held accountable in money laundering. Criminal convictions forcorporations may be imposed against the corporation if the criminal offense of moneylaundering performed or ordered by the personnel control corporation; carried outin order to meet the intent and objectives of the corporation; conducted inaccordance with the duties and functions of the perpetrator or the command, anddone with the intent to benefit the corporation.